Assessing pesticide leaching and desorption in soils with different agricultural activities from Argentina (Pampa and Patagonia) - Gonzalez, Mariana (2010)
Pesticide distribution in the soil profile depends on soil and pesticide properties as well as on the composition of irrigation water. Water containing surfactants, acids or solvents, may alter pesticide desorption from soil. The distribution of organochlorine pesticides (OCPs) in two Argentinean agricultural areas, Pampa and Patagonia, was evaluated. Furthermore, pesticide desorption from aged and freshly spiked soils was performed by the batch technique, using solutions of sodium oxalate and citrate, dissolved organic carbon (DOC), wastewater and surfactants. Patagonian soil showed the highest OCP levels (46.5-38.1 mg g-1 OC) from 0 to 30 cm depth and the predominance of p,p´-DDE residues reflected an extensive and past use of DDT. Pampean soil with lower levels (0.039-0.07 mg g-1 OC) was mainly polluted by the currently used insecticide endosulfan. Sodium citrate and oxalate, at levels usually exuded by plant roots, effectively enhanced desorption of p,p´-DDT,  p,p´-DDE and a-cypermethrin, while no effects were observed for a-endosulfan and endosulfan sulfate. The non-ionic surfactant Tween 80 behaved similarly to the acids, whereas the anionic sodium dodecyl sulfate enhanced desorption of all pesticides. Increased desorption of the hydrophobic pesticides also occurred when DOC from humic acids but not from sewage sludge or wastewater were used. Soil profile distribution of pesticides was in accordance with results from desorption studies. Data suggest pesticide leaching in Pampean and Patagonian soil, with risk of endosulfan to reach groundwater and that some organic components of wastewaters may enhance the solubilisation and leaching of recalcitrant compounds such as p,p´-DDT and p,p´-DDE.